1982
DOI: 10.1128/iai.36.2.802-810.1982
|View full text |Cite
|
Sign up to set email alerts
|

Experimental otitis media in gerbils and chinchillas with Streptococcus pneumoniae, Haemophilus influenzae, and other aerobic and anaerobic bacteria

Abstract: To ascertain the usefulness of Mongolian gerbils as an inbred model for otitis media, 52 Mongolian gerbils (Meriones unguiculatus, strain MON/Tum) were compared with 26 chinchillas (Chinchilla laniger) for susceptibility to Streptococcus pneumoniae type 3, Haemophilus influenzae type b, and a polymicrobic culture including anaerobes (Streptococcus intermedius, Propionibacterium acnes, Staphylococcus epidermidis, and Corynebacterium sp.). Organisms were inoculated percutaneously into the superior chamber of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
9
0

Year Published

1986
1986
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(11 citation statements)
references
References 27 publications
2
9
0
Order By: Relevance
“…Gram‐positive bacteria induced a more aggressive clinical picture with bulging tympanic membranes and more dilated vessels than the gram‐negative bacteria, which produced more often retracted tympanic membranes with relatively thin vessels in the rat model. These findings are similar to those reported from other animal models and humans (12, 13, 15). A red tympanic membrane is an established criterion for AOM.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Gram‐positive bacteria induced a more aggressive clinical picture with bulging tympanic membranes and more dilated vessels than the gram‐negative bacteria, which produced more often retracted tympanic membranes with relatively thin vessels in the rat model. These findings are similar to those reported from other animal models and humans (12, 13, 15). A red tympanic membrane is an established criterion for AOM.…”
Section: Discussionsupporting
confidence: 92%
“…The diagnosis of AOM rests today on the visualization of the tympanic membrane, its pathology, and the experience and skill of the examining physician. Studies in an established rat otitis model have indicated that different pathogens yield different otomicroscopic findings and host responses (11–15). The interleukin(IL)‐6 gene is rapidly expressed in the rat middle ear mucosa during AOM, and, in contrast to other cytokines, the rapidity is independent of etiology (16).…”
mentioning
confidence: 99%
“…It is also common that the cefuroxime MICs for such strains are higher than those of amoxicillin (12). In addition, this strain was able to induce AOM in gerbils, as described by other investigators (3,10).…”
Section: Discussionsupporting
confidence: 63%
“…AOM induced in gerbils is a well-established model for studying AOM as well as for comparing the efficacies of different antimicrobial regimens (3,10).…”
mentioning
confidence: 99%
“…Chinchilla, gerbil, and rat models have been developed to study OM (16,21,31), and among them, chinchillas provide the best available model for NTHi OM (19). Direct challenge of the ME with NTHi is more stringent and reliable than a nasopharyngeal challenge in terms of controlling the amount of bacteria introduced (1, 2, 21).…”
Section: Discussionmentioning
confidence: 99%